Stressors Among Medical Undergraduates During COVID 19 Era by Using Medical Students' Stressor Questionnaire (MSSQ-40) Scale - Ashutosh Jogia; Priyanka Jogia (Medsci Publications, 2022)
Introduction: Stress is defined as the body's non-specific response or reaction to demands made on it, or to disturbing events in the environment. It has been observed that medical school environments in India are extremely stressful and that this stress has led to suicide attempts by students. At the present time, the COVID-19 pandemic and its consequences are affecting everyone's day-to-day life, making medical students more stressed than ever. This study aimed to determine levels of stress in medical students during 2021. Methodology: A web-based cross-sectional study was conducted on first and second-year MBBS students of GMERS Medical College, Gandhinagar, Gujarat, India, using MSSQ-40, a standardized test for determining medical student stress levels. The data was entered and analyzed using MS Excel 2019 and significance was determined using the Mann Whitney U Test. Result: All students enrolled in the study scored between 1 and 2 in all six domains of the MSSQ, suggestive of a moderate degree of stress. The second-year students' scores were higher than those of the first-year students across all domains (1.32, 1.13, 1.11, 1.14, 1.03, and 1.14 in first years, indicative of mild stress, compared with 2.31, 2.10, 1.98, 1.91, 1.87, and 2.05 for second years, indicative of moderate to high stress). The difference was statistically significant in all six domains. Academic-related stress (ARS) received the highest score (1.32 for first years, and 2.31 for second years) followed by intrapersonal and interpersonal-related stressors (IRS) and group activities related stressors (GARS). The scores recorded in this study were comparable with those recorded in pre-pandemic studies, however, suggesting that COVID-19 is not a significant cause of the stress. Conclusion: Second year students were more stressed in all domains compared to first year students. We recommend reducing the number of exams; moving from a marking to a grading system of assessment to ease competition; introducing more ordered timetabling; targeting learning to focus on essential subjects only; and providing better training for group activities.